Thermal stress influence on the long-term performance of fast-charging paraffin-based thermal storage - Lahuri, Azizul Hakim (Elsevier, 2023)
The present study evaluates the impact of charging speeds on the long-term performance of paraffin-based thermal energy storage (TES) up to 10,000 actual thermal cycles. Paraffin and form-stable phase change material (FSPCM) is used as the reference materials. The FSPCM is made of paraffin (80 wt%) and high-density polyethylene (HDPE, 20 wt%). The thermal cycling treatment is applied to the samples using slow (1 °C/min), normal (5 °C/min) and fast-charging cycles (10 °C/min). Performance assessment is conducted using an active thermal storage model. According to the assessment, thermal stress and hysteresis effect occur severely after 10,000 fast-charging cycles. It disrupts the heat transfer process, reducing the power and charging rate. Scanning electron microscope (SEM) shows the void formation for paraffin which correspond to a lower efficiency (62.5 %) than FSPCM (66.6 %). The presence of HDPE reduces the impact of the fast-charging effect on paraffin. The SEM micrograph for FSPCM indicates that a chemi-crystallization leads to phase-separation between paraffin and HDPE. It helps to maintain the charging and discharging duration after 10,000 fast-charging cycles. Furthermore, the decrement of melting enthalpy of FSPCM (5.5 %) is much lower than paraffin (12.7 %). Hence, FPSCM maintains the storage capacity after 10,000 fast-charging cycles at a sufficient level. The multi-step transition and power curve during the charging/discharging cycle are discussed in detail within the article. Further improvement can be taken to minimize the performance degradation of fast-charging paraffin-based TES by compositing paraffin to withstand thermal stress or modifying the system operation after a certain fast-charging cycle.